Association between the dietary inflammatory index and all‐cause mortality in colorectal cancer long‐term survivors. Issue 6 (3rd December 2018) - Ratjen, Ilka; Shivappa, Nitin; Schafmayer, Clemens; Burmeister, Greta; Nöthlings, Ute; Hampe, Jochen; Hébert, James R.; Lieb, Wolfgang; Schlesinger, Sabrina
Abstract : Pro‐inflammatory dietary factors have been shown to be associated with the incidence of a range of cancers. However, there are many fewer studies on the association between the inflammatory potential of diet and survival after cancer diagnosis. We examined the association between post‐diagnosis dietary inflammatory index (DII®) scores and all‐cause mortality in long‐term survivors of colorectal cancer (CRC). DII scores were calculated from dietary data of 1, 404 CRC survivors collected at a median of 6 years after CRC diagnosis. Using multivariable‐adjusted Cox proportional hazards regression models, hazard ratios (HR) and 95% confidence intervals (CI) were estimated for the association of DII scores, modeled continuous and in quartiles, with all‐cause mortality. After a median follow‐up time of 7 years (after dietary assessment), 204 study participants had died. Overall, in the fully adjusted model there was a suggestion of a positive association between DII score and all‐cause mortality (HRDIIquartile4vs1 : 1.36; 95% CI: 0.88–2.09 and HRDIIcontinuous : 1.08; 95% CI: 0.97–1.20). However, in subgroup analyses, we found significant differences in individuals with metastatic disease (HRDIIcontinuous : 1.34; 95% CI: 1.07–1.67) and the absence of stoma (HRDIIcontinuous : 1.15; 95% CI: 1.02–1.29). Overall, the post‐diagnosis DII was not statistically significantly associated with all‐cause mortality in CRC long‐term survivors; however, there was suggestive evidence of an association in select subgroups. Abstract : What's new? High scores on the dietary inflammatory index (DII®), a method for quantifying the inflammatory potential of a person's diet, are associated with increased colorectal cancer (CRC) incidence. Little is known, however, about associations between DII scores and mortality after CRC diagnosis. Here, DII scores collected at a median of six years after diagnosis for more than 1, 400 long‐term CRC survivors suggests that overall the inflammatory potential of an individual's diet has no bearing on all‐cause mortality. In certain subgroups of patients, however, including those with metastatic disease or those without a stoma, evidence suggests high DII score is linked to increased all‐cause mortality.